Preheating effect on microhardness and depth of cure of three bulk-fill composite resins: An in vitro study - Aashna Sunil Sahetia; Divya Rupesh Jain; Padmaja Panditrao Sirsat; Meenal N. Gulve; Swapnil J. Kolhe; Surbhi P. Patel (Wolters Kluwer Medknow Publications, 2024)
Aim: The aim of this in vitro study was to evaluate and compare the effect of preheating on microhardness and depth of cure of three bulk-fill composite resins. Methods: Three bulk-fill composite resins were used; Group I: Filtek Bulk Fill, Group II: Beautifil Bulk Restorative and Group III: Tetric N Ceram Bulk Fill. Further each group was divided into two subgroups, Sub Group A: Discs were prepared using nonheated composite, Sub Group B: Discs were prepared using preheated composite. A total of 60 disc shaped specimens were prepared and microhardness (Vickers Microhardness Number [VHN]) of the top and bottom surfaces of the disc specimens were measured by Vickers microhardness tester. The ratio of the bottom surface VHN to the top surface VHN was used to calculate the depth of cure. Results: Preheated groups showed higher VHN values as compared to nonheated groups. Group II showed higher VHN value as compared to Group I in both subgroups. Group III showed the least VHN values in both subgroups. VHN values were maximum on top surfaces and minimum on the bottom surfaces for all the groups. It was found that the highest depth of cure was 0.71 while lowest depth of cure was 0.62. Conclusion: Preheating resulted in higher VHN values compared to nonheating. Top surface VHN values were better as compared to bottom surface VHN values for all groups. The depth of cure showed satisfactory results for all groups.